The system for assessment of anthropogenic contaminated soils on heavy metals content - Fatjejev, A.I.; Smirnova, E.B. (AgroChemistry and Soil Science, 2018)
The aim of the review article is to present a new conceptual approach to the soil quality assessment by the content of heavy metals in the modern context of soil quality and soil health concepts. The article shows the main problems of contaminated soil assessment in Ukraine and suggests the best ways of solving them from the point of the authors view. The new assessment system proposes the development of a modification criteria series for general and individual soil indexes, taking into account the buffering of soils, the presence of different pollutants, synergism, antagonism and bioavailability of heavy metals, crops tolerance and the possibility of mixing and diluting plant products with excessive and deficient trace elements content. The authors proposed to use the yield quality criteria by ecological-toxicological indicators in the algorithms for calculating soil indexes. Unlike soil diagnostics, plant testing allows to determine precisely the areal of phytotoxic industrial emissions and to identify soil areas where it is difficult or impossible to obtain uncontaminated agricultural products.